Evolving state grammar for modeling DNA and RNA structures - Kumar, Ajay; Kalra, Nidhi; Garhwal, Sunita (International Journal of Engineering and Technology, 2017)
In this paper, we represent bio-molecular structures (Attenuator, Extended Pseudoknot Structure, Kissing Hairpin, Simple H-type structure, Recursive Pseudoknot and Three-knot Structure) using state grammar. These representations will be measured using descriptional complexity point of views. Results indicate that the proposed approach is more succinct in terms of production rules and variables over the existing approaches. Another major advantage of the proposed approach is state grammar can be represented by deep pushdown automata, whereas no such automaton exists for matrix ins-del system.